Phylogenetic Star Contraction Applied to Asian and Papuan mtDNA Evolution - Peter Forster; Antonio Torroni; Colin Renfrew; Arne Röhl (2001)
In the past decade, mitochondrial DNA (mtDNA) of 826 representative East Asians and Papuans has been typed by high-resolution (14-enzyme) restriction fragment length polymorphism (RFLP) analysis. Compared with mtDNA control region sequencing, RFLP typing of the complete human mitochondrial DNA generally yields a cleaner phylogeny, the nodes of which can be dated assuming a molecular clock. We present here a novel star contraction algorithm which rigorously identifies starlike nodes (clusters) diagnostic of prehistoric demographic expansions. Applied to the Asian and Papuan data, we date the out-of-Africa migration of the ancestral mtDNA types that founded all Eurasian (including Papuan) lineages at 54,000 years. While the proto-Papuan mtDNA continued expanding at this time along a southern route to Papua New Guinea, the proto-Eurasian mtDNA appears to have drifted genetically and does not show any comparable demographic expansion until 30,000 years ago. By this time, the East Asian, Indian, and European mtDNA pools seem to have separated from each other, as postulated by the weak Garden of Eden model. The east Asian expansion entered America about 25,000 years ago, but was then restricted on both sides of the Pacific to more southerly latitudes during the Last Glacial Maximum around 20,000 years ago, coinciding with a chronological gap in our expansion dates. Repopulation of northern Asian latitudes occurred after the Last Glacial Maximum, obscuring the ancestral Asian gene pool of Amerinds.